2023
DOI: 10.1186/s12880-023-01058-7
|View full text |Cite
|
Sign up to set email alerts
|

Periaortic adipose radiomics texture features associated with increased coronary calcium score—first results on a photon-counting-CT

Abstract: Background Cardiovascular diseases remain the world’s primary cause of death. The identification and treatment of patients at risk of cardiovascular events thus are as important as ever. Adipose tissue is a classic risk factor for cardiovascular diseases, has been linked to systemic inflammation, and is suspected to contribute to vascular calcification. To further investigate this issue, the use of texture analysis of adipose tissue using radiomics features could prove a feasible option. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Radiomics features for differentiation based on the periaortic adipose tissue textures were identified using Random Forest-based feature selection on the Groups of Agatston score 0 and ≥100 and investigated in the Group of 1-99 for internal validation. It was found that two radiomics features differed between the groups, one of them significantly [17]. While the investigated adipose tissues as well as the identified radiomics features differ from our study, it nevertheless supports our findings, as it underlines the feasibility of distinguishing between patients with and without CAC using radiomics texture features of adipose tissues, indicating a potential underlying diffuse fibrotic or inflammatory reaction, which can be detected by texture analysis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Radiomics features for differentiation based on the periaortic adipose tissue textures were identified using Random Forest-based feature selection on the Groups of Agatston score 0 and ≥100 and investigated in the Group of 1-99 for internal validation. It was found that two radiomics features differed between the groups, one of them significantly [17]. While the investigated adipose tissues as well as the identified radiomics features differ from our study, it nevertheless supports our findings, as it underlines the feasibility of distinguishing between patients with and without CAC using radiomics texture features of adipose tissues, indicating a potential underlying diffuse fibrotic or inflammatory reaction, which can be detected by texture analysis.…”
Section: Discussionsupporting
confidence: 80%
“…To find ways to extend the diagnostics of such patients at risk, research on EAT properties with potential diagnostic use has increased over the last few years. While these studies have often been based on the volume [14,15] of the adipose tissue, more recent studies have conducted radiomics examinations of perivascular intrathoracic adipose tissue with first promising results [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Gray-Level Co-occurrence Matrix (GLCM) methods, as proposed by Haralick 39 , are based on the estimation of the second-order joint conditional probability density functions, which characterize the spatial relationships between pixels. GLCM is commonly used in texture analysis 40 , 41 , for instance in radiomics on CT-scan or MRI images 42 44 or for skin texture assessment 45 . In GLCM, the co-occurrence matrix contains information on entropy, homogeneity, contrast, energy and correlation between pixels.…”
Section: Methodsmentioning
confidence: 99%